A 3-Dimensional Printed Patient-Specific Surgical Guide to Facilitate Transsphenoidal Hypophysectomy in Dogs - Escauriaza, Leticia; Fenn, Joe; McCue, John; Roper, Darren; Vandenberghe, Helene; Nye, George; Oxley, Bill; Granger, Nicolas (Frontiers in Veterinary Science, 2022)
Objective Hypophysectomy in dogs is a difficult surgery that requires specific learning and training. We aimed to evaluate the accuracy of a 3-dimensional printed patient-specific surgical guide to facilitate choosing the entry point in the basisphenoid bone before approaching the sella turcica during transsphenoidal hypophysectomy in dogs. Methods Two canine cadavers and 8 dogs undergoing transsphenoidal hypophysectomy for Cushing’s disease treatment, involving design and fabrication of a 3-dimensional printed guide. The ideal entry point in the basisphenoid bone outer cortical layer was determined in each dog pre-operatively; its anatomical location was described with a set of measurements then compared to post-operative computed tomography measures describing the location of the outer cortical window created in the basisphenoid bone. Results Several guide designs were proposed, and a consensus reached based on surgeons’ experience performing hypophysectomy. The device chosen could be applied to the size and shape of skulls encountered in this case series. The pre-planned measurements were comparable to post-operative measurement (there was also no statistical difference), with median of differences < 0.1mm, which we judged as clinically acceptable. Clinical significance Hypophysectomy in dogs is a challenging procedure that has a learning curve and needs to be performed by specialist neurosurgeons. We propose that a low-profile 3-dimensional printed surgical guide can aid the specialist neurosurgeon to locate the burring site of the outer cortical layer of the basisphenoid bone at a pre-defined location and with good accuracy. It does not alleviate the need to understand the anatomy of the region and to know how to create a slot within the basisphenoid bone, which remains essential to enter the sella turcica. This device could help specialist veterinary neurosurgeons wishing to be trained to perform hypophysectomy.